Plasmodium parasite exploits host aquaporin-3 during liver stage malaria infection - Dora Posfai; Kayla Sylvester; Anupama Reddy; Jack G. Ganley; Johannes Wirth; Quinlan Cullen; Tushar Dave; Nobutaka Kato; Sandeep S. Davé; Emily R. Derbyshire (2018)
Within the liver a single Plasmodium parasite transforms into thousands of blood-infective forms to cause malaria. Here, we use RNA-sequencing to identify host genes that are upregulated upon Plasmodium berghei infection of hepatocytes with the hypothesis that host pathways are hijacked to benefit parasite development. We found that expression of aquaporin-3 (AQP3), a water and glycerol channel, is significantly induced in Plasmodium-infected hepatocytes compared to uninfected cells. This aquaglyceroporin localizes to the parasitophorous vacuole membrane, the compartmental interface between the host and pathogen, with a temporal pattern that correlates with the parasite's expansion in the liver. Depletion or elimination of host AQP3 expression significantly reduces P. berghei parasite burden during the liver stage and chemical disruption by a known AQP3 inhibitor, auphen, reduces P. falciparum asexual blood stage and P. berghei liver stage parasite load. Further use of this inhibitor as a chemical probe suggests that AQP3-mediated nutrient transport is an important function for parasite development. This study reveals a previously unknown potential route for host-dependent nutrient acquisition by Plasmodium which was discovered by mapping the transcriptional changes that occur in hepatocytes throughout P. berghei infection. The dataset reported may be leveraged to identify additional host factors that are essential for Plasmodium liver stage infection and highlights Plasmodium's dependence on host factors within hepatocytes.